Long-term effects of early-life rumen microbiota modulation on dairy cow production performance and methane emissions - Huuki, Hanna; Tapio, Miika; Mäntysaari, Päivi; Negussie, Enyew; Ahvenjärvi, Seppo; Vilkki, Johanna; Vanhatalo, Aila; Tapio, Ilma (Frontiers in Microbiology, 2022)
Rumen microbiota modulation during the pre-weaning period has been suggested as a mean to affect animal traits and production performance later in life. In this study we examined whether early life inoculation of monozygotic twin calves with fresh rumen liquid from an adult cow has a beneficial effect on rumen microbiome development post-weaning and assessed the possible long-term effect on production traits and methane emissions during their first lactation period. Animal weight gain and rumen fermentation parameters were monitored in treated and control heifers (n=4 each) from 2 to 12 months of age. The rumen bacteria were determined by using the 16S rRNA, ciliate protozoa - 18S rRNA gene and anaerobic fungi - ITS1 amplicon sequencing. The milk production and quality, feed efficiency and methane emissions were monitored during their first lactation. Apart from archaea, the richness of bacteria and ciliate protozoa increased until month 7, and anaerobic fungi until month 11. Microbial community development reached maturity between 6 to 10 months of age. Treated heifers showed significant differences in bacterial community composition in month 2 and these differences remained until month 6, after which treated, and control heifers became similar. The differences between the groups in taxonomic abundances of archaea and ciliate protozoa occurred until month 3, while treatment had no effect on post-weaning anaerobic fungi development. Random forest prediction of age showed that the prokaryote community in the treated group was 0.75 months ahead of the maturity of the control group in month 4, and 1.5 months ahead of the maturity in ciliate protozoa community in month 2. No difference in the maturity of anaerobic fungi community was observed. The treated heifers had lower variation in energy corrected milk yield and residual energy intake as well as lower somatic cell count throughout their 1st lactation period, but no differences between the groups in methane emissions were observed. Our results demonstrated that the orally administered microbial inoculant induced transient early rumen microbiome maturation. In addition, the treatment may influence the later production performance, although the mechanisms that mediate these effects need to be further explored.